Proteomics of mouse cortex following conditional deletion of Psmc1 proteasomal subunit in neurones - Elkharaz, Jamal Ibrahim (2013)
Neurodegenerative diseases are characterized by progressive degeneration of selective neurones in the nervous system and the formation of protein inclusions in surviving neurones. The mechanisms underlying neurodegeneration and neuroprotection in the nervous system remain elusive. Ubiquitin is one of the hallmarks of neuropathological inclusions in the majority of neurodegenerative diseases, including Alzheimer’s disease and Parkinson’s disease. Therefore, dysfunction of the ubiquitin proteasome system has been implicated in disease cause and/or progression. This thesis investigates a unique conditional genetic mouse model of neurodegeneration caused by conditional genetic 26S proteasomal depletion in mouse forebrain neurones. We have identified potential proteins targeted for ubiquitination in brain using bio-affinity chromatography of zinc finger protein ZNF216 coupled with mass spectrometry. This lead to the identification of several potential ubiquitinated proteins involved in gene expression and regulation. We have also investigated the global brain proteome in response to 26S proteasomal depletion in neurones using two-dimensional fluorescence difference in-gel electrophoresis coupled to mass spectrometry for protein identification. Several differentially expressed proteins were identified in the 26S proteasome-depleted cortex. Astrocytic intermediate filament proteins glial acid fibrillary protein and vimentin, as well as the antioxidant peroxiredxoin-6, were upregulated. Mitochondrial fumarate hydratase and stathmin-1, involved in the tricarboxylic acid cycle and cytoskeletal microtubule dynamics respectively, were downregulated. These proteins have been validated by biochemical and immunohistochemical approaches. Further analysis of oxidative stress revealed increased lipid and protein oxidation that may be involved in the neurodegeneration associated with 26S proteasomal depletion. However, we also show increased phospholipase A2 activity associated with peroxiredoxin-6 expression that may have additional roles in neurodegenerative and/or neuroprotective functions. Interestingly, the levels of reactive oxygen species were inversely correlated with the upregulation of peroxiredoxin-6. We suggest that peroxiredoxin-6 may play an important role in the brain in the protection against oxidative stress and our studies may improve our physiological and pathological understanding of neurodegenerative disease.